HUMAN RESOURCE PRACTICES FOR TEACHING PERSONNEL OF SELECTED PRIVATE ASIAN HIGHER EDUCATIONAL INSTITUTION - Ventayen, Randy (MATTER: International Journal of Science and Technology, 2017)
Manpower is considered as the most important asset of every institution, this is the reason why employee satisfaction and retention play an important role for any institution. Satisfied employees tend to be more provide better outputs for being creative, productive and committed to their employers while dissatisfied employees sometimes don't provide quality outputs. Institutions who can create work environments that attract, motivate and retain hard-working individuals will succeed in terms of profit. This study investigated the job satisfaction of teaching personnel of selected higher educational institution in Pangasinan, specifically 3 private higher education institution. It sought to answer what benefits being received by the teaching personnel, how are they satisfied in terms of professional growth, promotion, pay, work and career plan and the reason of teaching personnel leading to job satisfaction. Based on the result of the study, the majority of the respondents agreed that salary play a major role in satisfaction. As a result of their perspective towards their work, a large portion of the respondents agree that they will look for a new job next year, quit their present job and see that there is not much prospect with regards to their present organization. The majority of the respondents claim that companies must increase the salary for a private institution, while only a few of the population claim that companies should motivate employees across diverse population within the company.